Evidence based medical use of aloe vera extracts, short review of literature - Samer N. Samarh; Najm A. Khalaf; Mohammed M. Hajhamad (Medip Academy, 2024)
The use of aloe vera is being promoted for a large variety of conditions. The aim of this review was to summarize all available research papers on aloe vera preparations with a view to providing evidence for or against its clinical effectiveness. Independent literature searches were conducted in PubMed. All studies of controlled clinical trials, observational studies and case series were included. There were no restrictions on the language of publication. All studies were read by all authors and data were extracted in a standardized, pre-defined manner. Even though there are some promising results, clinical effectiveness of oral or topical aloe vera is not sufficiently defined at present.